Dimensiunile bunăstării factorului uman în contextul mediului dinamic al societății - Balmuş-Andone, Mihaela (Editura USM, 2024)
A major concern for humanity in the contemporary world is the well-being of the population. The concept of “population well-being” encompasses multiple dimensions, including various aspects of human life. Generally, the improvement of individuals' well-being relies on two main sources: the economy, which provides the financial resources necessary for a decent living and the social policies which act as a guarantee for the population to thrive. However, it is known that human development models based solely on economic growth are incomplete or not enough. Thus, the research methodology is based on addressing various perspectives regarding the multidimensionality of well-being. These perspectives are synthesized from various bibliographic sources, as well as methodologies proposed by international organizations focused on this area. The conclusions reflect the complexity of the concept, including its perception (objective or subjective). In the same vein, it is worth highlighting that reduced welfare has significant downsides and extends far beyond than just how the employees feel.
The dimensions of human well-being in the context of the dynamic environment of society
Keywords: human factor; well-being dimensions; dynamic environment factors; costs